2015
DOI: 10.3382/ps/pev275
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fructooligosaccharide supplementation on growth performance, intestinal morphology, and immune responses in broiler chickens challenged with Salmonella Enteritidis lipopolysaccharides

Abstract: This study was conducted to examine the effects of fructooligosaccharide (FOS) supplementation on growth performance, lymphoid organ weight, intestinal morphology, and immunological status in broilers (n=180) challenged with Salmonella Enteritidis lipopolysaccharides (LPS). Birds were randomly assigned into a 3×2 factorial arrangement that included 1) 3 dietary treatments from d one to 21: positive control (PC), wheat-corn-soybean meal based diet contained antibiotics (virginiamycin and monensin); negative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 33 publications
5
61
1
Order By: Relevance
“…Yet, FCR of birds fed 0.4% of AY was better (P = 0.04) than birds supplemented with 0.2% of AY or the unsupplemented birds (negative control). Studies have demonstrated the potential use of yeast cell components in the diets of broiler chickens (Zhang et al, 2005;Gao et al, 2008;Shang et al, 2015;Alizadeh et al, 2016). Gao et al (2008) supplemented AY to broiler chickens and did not find difference in the growth performance from d 1 to 21.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Yet, FCR of birds fed 0.4% of AY was better (P = 0.04) than birds supplemented with 0.2% of AY or the unsupplemented birds (negative control). Studies have demonstrated the potential use of yeast cell components in the diets of broiler chickens (Zhang et al, 2005;Gao et al, 2008;Shang et al, 2015;Alizadeh et al, 2016). Gao et al (2008) supplemented AY to broiler chickens and did not find difference in the growth performance from d 1 to 21.…”
Section: Resultsmentioning
confidence: 97%
“…The use of prebiotics, such as whole yeast (Saccharomyces cerevisiae), as well as carbohydrates isolated from its cellular wall (mannan-oligosaccharides-MOS, fructooligosaccharides-FOS, and β-glucans) has been the focus of several studies in poultry (Shanmugasundaram and Selvaraj, 2012;Shao et al, 2013;Shang et al, 2015Shang et al, , 2018Adhikari et al, 2018). Nucleotides, isolated from the cytoplasm of yeast, have also been tested in broiler chickens (Uauy, 1994;Carver and Walker, 1995;Mateo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS-induced structural damage of the intestinal mucosal barrier was reversed with dietary STE supplementation. It has been reported that natural extract with anti-inflammatory effect can restore the damaged intestinal morphology in LPS-challenged broilers [37,38]. The down-regulation of TLR4/NF-κB signaling and reduced mRNA expression of pro-inflammatory cytokines might be one of the reasons that intestinal integrity improved in the LPS + STE group.…”
Section: Discussionmentioning
confidence: 95%
“…Intestinal mucosa evaluation can provide information on health status in poultry as stressors such as enteric infections may lead to structural modifications [ 6 , 32 , 33 ]. We found similar histopathological features regardless of the age of infection in both the duodenum and cecum of broilers.…”
Section: Discussionmentioning
confidence: 99%